Pengaruh Kemampuan Verbal dan Kemampuan Numerik Terhadap Kemampuan Menyelesaikan Soal Sistem Persamaan Linear Bentuk Cerita - Median Aulia Azmi; Nyoman Sridana; Arjudin Arjudin; Baidowi Baidowi (Griya Journal of Mathematics Education and Application, 2021)
This study aims to determine the effect of verbal ability and numerical ability, the effect of verbal ability, and the effect of numerical ability on the ability of solving linear equation system problems. This study is an ex post facto research. The population of this study were students of class XI SMAN 9 Mataram. The sample in this study were 28 students of class XI SMAN 9 Mataram represented by four students in each class. The data analysis used is multiple linear regression analysis and simple linear regression analysis. From the results of the data analysis, there is a significant influence between verbal ability and numerical ability on the ability to solve linear equation system problems with a value of Fhitung = 3,660 > Ftabel = 3,39. The magnitude of this influence is written in the form of a regression equation, namely Y = 24,602 + 0,140X1 + 0,224X2. This regression equation shows that if the verbal ability score increases by 1 with a fixed numerical ability score, then the ability to solve math problems will increase by 0,140; and if the numerical ability score increases by 1 with a fixed verbal ability score, the value of the ability to solve story questions will increase by 0,225 and plus 24,602 from other factors.